(untitled) - Nguyen, Duy Khien (Hà Nội, 1998)
This book aims to heip foreign businesses better understand the business environment as well as the legal framework for starting their own business and investment projects in Vietnam.
Keywords: Commerce,Economic conditions; Handbooks, manuals, etc.,Handbooks, manuals, etc